99DOTS: Using Mobile Phones to Monitor Adherence to Tuberculosis Medications - Cross, Andrew; Rodrigues, Rashmi; D'Souza, George; Thies, Bill (Global mHealth Forum. Washington, D.C, 2014)
The WHO estimates that even in developed countries, less than half of chronic disease patients take medication as directed. This problem is especially dire in the case of tuberculosis (TB), where non-adherence to medication contributed to an estimated 450,000 drug-resistant cases in 2013. To bolster adherence, countries such as India have long embraced Directly Observed Therapy, Short course (DOTS), where patients travel to clinics to take doses under the observation of a care provider. However, DOTS has proven to be costly, difficult to implement, and inconvenient for patients. These factors greatly limit its reach and effectiveness.